2018
DOI: 10.22270/jddt.v8i5-s.1989
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Microemulsion of Curcumin for the Management of Osteoarthritis

Abstract: Curcumin (diferuloylmethane) is a natural polyphenolic compound with potent anti-inflammatory, anticancer and antioxidant activities. However, its bioavailability is low as it is poorly absorbed in the gastrointestinal tract. Microemulsions offer the potential to improve the solubility and bioavailability of bioactive compounds; the present work investigated the topical delivery potential of microemulsion gel loaded with curcumas. Curcumin microemulsion was prepared by spontaneous emul­sification method using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Based on the previously determined calibration curve, the maximum amount of Curcumin that can be solubilized in LVM microemulsion and gel microemulsions was identified ( Figure 4 ). The maximum Curcumin capacity that could be encapsulated in the LVM microemulsion (1.69 wt.%, Figure 4 ) was approximately 2-fold higher than in the microemulsion prepared with oleic acid, Smix (ethanol and Tween 80, Span 80, n-butanol) and water, as described by S. Sharma et al [ 43 ]. In the case of gel microemulsions, there was generally a very small increase in the incorporation capacity of Curcumin ( Figure 4 ) compared to simple microemulsion, probably due to the interaction between drug molecules and polyelectrolyte chains.…”
Section: Resultsmentioning
confidence: 54%
“…Based on the previously determined calibration curve, the maximum amount of Curcumin that can be solubilized in LVM microemulsion and gel microemulsions was identified ( Figure 4 ). The maximum Curcumin capacity that could be encapsulated in the LVM microemulsion (1.69 wt.%, Figure 4 ) was approximately 2-fold higher than in the microemulsion prepared with oleic acid, Smix (ethanol and Tween 80, Span 80, n-butanol) and water, as described by S. Sharma et al [ 43 ]. In the case of gel microemulsions, there was generally a very small increase in the incorporation capacity of Curcumin ( Figure 4 ) compared to simple microemulsion, probably due to the interaction between drug molecules and polyelectrolyte chains.…”
Section: Resultsmentioning
confidence: 54%
“…The curcumin microemulsion encapsulating performance was 88 ± 1.5%. Sharma et al reported an EE of 69.98 ± 0.21 to 83.32 ± 0.15% for curcumin-loaded Pluronic F-127 microemulsions [ 83 ]. Chen et al prepared curcuminoid microemulsions consisting of soybean oil, Tween 80, ethanol, and water with an EE of 85.7% [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is a significant achievement potentially enabling a prolonged therapeutic effect. In a previous study, Sharma et al reported that curcumin release of about 74% in 8 h for optimized microemulsion formulations [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…The microemulsion sample subjected to-20 ᵒC for 24 h and then another 24h at 40 ᵒC . The physical stability of microemulsion was examined by measuring globule size and polydispersity index before and after the freeze-thaw cycle and centrifugation [19].…”
Section: Freeze-thaw Cyclementioning
confidence: 99%
“…The average globule size, polydispersity index, and zeta potential of the curcumin-loaded emulgel were determined by dispersed gel into distilled water, and kept for sonication (20-30 s) and after that for vortexed for 1 min to make sure that to minimize the aggregation if present in microemulsion gel [19]. After that, the sample was analyzed for average globule size, polydispersity index, and zeta potential by using Zetasizer (Nano ZS: Malvern Instruments.…”
Section: Globule Size and Polydispersity Index And Zeta Potential Analysismentioning
confidence: 99%